2015
DOI: 10.11622/smedj.2015091
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of epidemiological risk factors for ingestion of fish bones in Singapore

Abstract: INTRODUCTIONIngestion of fish bones is a common clinical complaint among adult patients. The aim of this study was to evaluate the epidemiological and behavioural risk factors for fish bone ingestion. METHODS RESULTSThe wearing of dentures, the use of utensils to eat fish and the practice of deboning fish in one's mouth were found to be associated with an increased risk of fish bone ingestion.CONCLUSION To prevent the occurrence of fish bone ingestion and its possible complications, at-risk populations should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 10 publications
2
16
0
Order By: Relevance
“…As to fish bones, the incidence among Chinese patients was a lot higher as compared with other Asian patients. 27 This may be associated with following reasons: deboning fish in mouth, eating fish with chopsticks, and wearing dentures while eating fish. 27,28 To avoid such incidence and accidental denture ingestion, dental implants is advised instead of removable dentures for the seniors, especially for patients with seizure and Alzheimer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As to fish bones, the incidence among Chinese patients was a lot higher as compared with other Asian patients. 27 This may be associated with following reasons: deboning fish in mouth, eating fish with chopsticks, and wearing dentures while eating fish. 27,28 To avoid such incidence and accidental denture ingestion, dental implants is advised instead of removable dentures for the seniors, especially for patients with seizure and Alzheimer.…”
Section: Discussionmentioning
confidence: 99%
“…27 This may be associated with following reasons: deboning fish in mouth, eating fish with chopsticks, and wearing dentures while eating fish. 27,28 To avoid such incidence and accidental denture ingestion, dental implants is advised instead of removable dentures for the seniors, especially for patients with seizure and Alzheimer. 7 In this study, about half of patients had odynophagia and sore throat.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of FFBs vary according to the fish availability, the method of cooking and the eating habits. 1 7 12 Most patients cannot recall and identify the type of the ingested fish. 9 No specific method of cooking is considered to be a risk factor, but some studies indicated that stewed fish causes the highest number of cases of esophageal FFBs, followed by baked fish, steamed fish, and raw fish.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…1 2 The use of chopsticks or cutlery to eat boned fish, fish deboning in the mouth, and wearing dentures while eating are also recognized as risk factors for FFBs. 12…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation